Case Report: Chronic hepatitis E in a hematopoietic stem cell transplant recipient: The first report of hepatitis E virus genotype 4 causing chronic infection in a non-solid organ recipient - Chen, Zihao; Wei, Junfeng; Jiang, Li; Ying, Dong; Tian, Weikun; Zhang, Mengyang; Wen, Guiping; Wang, Siling; Liu, Chang; Wang, Yingbin; Wu, Ting; Tang, Zimin; et al. (Frontiers in Immunology, 2022)
Hepatitis E virus (HEV) is one of important public health issue around the world, and chronic HEV infection has been reported in immunosuppressed individuals. This study reported a male case, with very severe aplastic anemia (AA), developed chronic hepatitis E after hematopoietic stem cells transplantation (HSCT). Abnormal alanine aminotransferase (ALT) appeared since HSCT and persisted for 27 months. The case was seropositive for anti-HEV IgG and IgM after HSCT. Twenty-two months after HSCT, HEV nucleic acid and antigen (HEV RNA and Ag) testing were positive and persisted for 5 and 10 months, respectively. Positive stains of HEV Ag were present in liver biopsy sample. The case rapidly developed liver cirrhosis and was rescued by a regimen of oral ribavirin. These suggested the risk of HEV infection in HSCT recipients should be concerned.